2014
DOI: 10.1103/physrevb.90.125304
|View full text |Cite
|
Sign up to set email alerts
|

Tunable magnetic properties of transition metal dopedMoS2

Abstract: We report a detailed investigation of the electronic and magnetic properties of the transitionmetal (TM) doped two-dimensional (2D) MoS 2 using ab initio calculations. The doping is achieved by substituting two or more Mo-atoms by TM-atoms of the 3d-series. Additionally, the effect of codoping on the 2D-MoS 2 by cation-cation and cation-anion pairs is also investigated. Our results demonstrate that the TM-doping of 2D-MoS 2 leads to a significant reduction of the energy gap and the appearance of magnetic featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(103 citation statements)
references
References 46 publications
1
101
1
Order By: Relevance
“…On graphene, RKKY interactions with a dominant 1D character have been identified for impurities near the sample edges [25] and line defects [26]. Magnetic impurities, such as Mn, Fe [27,28], Co [28], or Ti [29], can be introduced by STM and/or associated with Mo or S vacancies.…”
mentioning
confidence: 99%
“…On graphene, RKKY interactions with a dominant 1D character have been identified for impurities near the sample edges [25] and line defects [26]. Magnetic impurities, such as Mn, Fe [27,28], Co [28], or Ti [29], can be introduced by STM and/or associated with Mo or S vacancies.…”
mentioning
confidence: 99%
“…Recently, the doping effects on the magnetic properties of monolayer MoS 2 were studied using first-principles calculations [24][25][26][27]. In particular, Cheng et al [24] indicated that (Mo, X)S 2 (X = Mn, Fe, Co, and Zn) are the promising system of 2D diluted magnetic semiconductor.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 Furthermore MoS 2 materials are predicted to be very suitable for spintronics applications due to their specially well-defined spin-splitting property, 8,9 and diverse magnetic orderings have been reported theoretically in transition-metal (TM) doped MoS 2 . [10][11][12][13][14] These studies verified that the electronic and magnetic properties of MoS 2 materials can be modified by TM dopants, which may lead to a new class of thin dilute magnetic semiconductors (DMS) in the engineering field. Be similar with MoS 2 monolayer structurally and electronically, the WS 2 monolayer has special electronic and magnetic characteristics and attracted more and more attention.…”
Section: Introductionmentioning
confidence: 84%
“…Similarly, there are five S atoms around two Ni atoms carry a total moment of -0.273 µ B . From the previous studies, 12,28 we know that the hybridization between the localized Ni 3d and the delocalized S 3p states leads to the AFM coupling between the Ni spins and S spins. More importantly, every time the S spins come cross a Ni defect, the AFM alignment between S and Ni leads to an effective FM alignment of all the Ni spins.…”
Section: -5mentioning
confidence: 99%